2014
DOI: 10.1002/micr.22249
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of tetanus toxin on sciatic nerve regeneration: A preliminary experimental study in rats

Abstract: This preliminary study firstly demonstrated the effectiveness of TeTx on nerve repair in experimental sciatic rat model based on functional, electromyographic and histological parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…A variety of therapeutic modalities have been adopted by physicians to achieve recovery in animal models, yet attaining fully functional recovery is still a challenge to be addressed ( Hussain et al, 2020 ). Many antioxidants (vitamin E, ubiquinone, and L-carnitine) ( Karsidag et al, 2012 ; Azizi et al, 2014 ; Moradi et al, 2014 ), anti-inflammatories (dexamethasone and acetylsalicylic acid) ( Subbanna et al, 2007 ; Feng and Yuan, 2015 ), or other substances (diphosphocholine, rapamycin, and tetanus toxin) ( Gunay et al, 2014 ; Ding et al, 2015 ; Emril et al, 2016 ) have been tried. However, few effective clinical drug treatments are available.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of therapeutic modalities have been adopted by physicians to achieve recovery in animal models, yet attaining fully functional recovery is still a challenge to be addressed ( Hussain et al, 2020 ). Many antioxidants (vitamin E, ubiquinone, and L-carnitine) ( Karsidag et al, 2012 ; Azizi et al, 2014 ; Moradi et al, 2014 ), anti-inflammatories (dexamethasone and acetylsalicylic acid) ( Subbanna et al, 2007 ; Feng and Yuan, 2015 ), or other substances (diphosphocholine, rapamycin, and tetanus toxin) ( Gunay et al, 2014 ; Ding et al, 2015 ; Emril et al, 2016 ) have been tried. However, few effective clinical drug treatments are available.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several reports indicate that the C-terminus may have an antiapoptotic effect on neurons [ 5 – 7 ] . Both in vitro and in vivo studies have shown that the TTC induces neuroprotection [ 5 , 8 , 9 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…An accumulation of released neurotrophins, e.g., brain‐derived neurotrophic factor (BDNF) or nerve growth factor (NGF), is postulated in the isolated local regenerative milieu within conduits . Recent studies investigate effects of additional administration of platelet rich plasma and platelet rich fibrin in silicone tubes or tetanus toxin on side of sciatic nerve lesion to facilitate nerve regeneration . Also various growth factors, like IGF‐1 or VEGF, were locally applied to improve peripheral nerve regeneration .…”
mentioning
confidence: 99%
“…2 Recent studies investigate effects of additional administration of platelet rich plasma and platelet rich fibrin in silicone tubes or tetanus toxin on side of sciatic nerve lesion to facilitate nerve regeneration. 4,5 Also various growth factors, like IGF-1 or VEGF, were locally applied to improve peripheral nerve regeneration. 6,7 For longer nerve gaps, nerve conduits serve as guiding structures for sprouting axons.…”
mentioning
confidence: 99%